The effect of contact time of adsorbent made from palm oil mill boiler ash on crude palm oil quality. Issue 3 (June 2021) - Mayyoga, S; Rangkuti, I U P; Purwanto, H
Abstract: Indonesia as an agricultural country, produces agricultural products and their waste. To increase the utilization of agricultural waste, hence Palm Oil Mill Boiler Ash processed into an adsorbent. This research aimed to determine the effect of contact time on the quality adsorption process of crude palm oil using adsorbent from Palm Oil Mill Boiler Ash. The results showed that the optimum contact time at 60 minutes resulted in the largest reduction in free fatty acids by 2.99% with a decrease in the percentage of 21.43%. The minimum water content of crude palm oil was 0.26% with a decrease in the percentage of 18.75%. Meanwhile, the impurities obtained in crude palm oil are around 0.299% - 0.312%. This showed that the boiler ash adsorbent, originating from the Palm Oil Mill, which activated with H3 PO4, is effective in reducing free fatty acids and water content in crude palm oil.